Valued-Based Selling Capability and Marketing Support Advantage: Suggestions and an Assessment Of Past Research To Improve the Sales of a Shipping Company - ., Kundori; ., Sukrisno (KnE Social Sciences, 2023)
To boost sales performance through marketing and a focus on entrepreneurship, this study developed and suggested a new fundamental model by adopting a variable valued-based selling capability. The model was tested on 110 respondents who were chosen through purposive sampling from a shipping business in Surabaya. Four hypotheses were suggested using quantitative research methods with Amos 22 as a data analysis tool. The results showed that the concept successfully drove sales performance, so the valued-based selling capability became an indicator of the key to success, demonstrating different marketing strategies for improving sales performance. Keywords: Marketing Support Advantage, Entrepreneurial Orientation, Valued Based Selling Capability, Sales Performance